The effectiveness of teaching Arabic language using the book al-Arabiyah baina Yadaik to improve the Arabic speaking skill of eighth grade students at Dar al-Naîm Islamic Yunior High School in Simpang Kubu Kampar/Fa’aliyatu Ta’limi al-Lughah al-Arabiyah biistikhdami Kitabi al-Arabiyah baina Yadaik Litarqiayti Maharah al-Kalam bi al-Lughah al Arabiyah lada Talamizi as-Shaffi at-Tsamini fi al-Madrasati Dar an-Na’im al-Mutawasshitah al-Islamiyah Simpang Kubu Kampar - Haya, Wirdatul; Zulkifli, Zulkifli; Asrofi, Asrofi (Al-Manar, 2023)
It was experiment research aimed at finding out the effectiveness of Arabic Language learning with Al Arabia Baina Yadaik book in increasing student Arabic speaking skills at the eighth grade of Islamic Junior High School of Darun Na’im Simpang Kubu, Kampar.  The formulation of the problem in this research was “was Arabic Language learning with Al Arabia Baina Yadaik book effective in increasing student Arabic speaking skills at the eighth grade of Islamic Junior High School of Darun Na’im Simpang Kubu, Kampar?”.  This research was started from planning the lesson plan, implementing, observing, and testing.  Arabic Language subject teachers and all the eighth-grade students at Islamic Junior High School of Darun Na’im Simpang Kubu, Kampar in the Academic Year of 2022/2023 were the population of this research, and the samples were the eighth-grade students of class 2 as the experiment group and the students of class 1 as the control group.  The subjects of this research were the eighth-grade students of classes 1 and 2 at Islamic Junior High School of Darun Na’im Simpang Kubu, Kampar.  The object was the effectiveness of Arabic Language learning with Al Arabia Baina Yadaik book in increasing student Arabic speaking skills at the eighth grade of Islamic Junior High School of Darun Na’im Simpang Kubu, Kampar.  Observation and test were the instruments of collecting data.  Based on data analysis, it could be concluded that Arabic Language learning with Al Arabia Baina Yadaik book was effective in increasing student Arabic speaking skills at the eighth grade of Islamic Junior High School of Darun Na’im Simpang Kubu, Kampar because the score of to 3.71 was higher than tt 2.563 at 1% significant level and 2.074 at 5% significant level.  It meant that H0 was rejected and Ha was accepted.  Based on the result of observation, the result was 95%, and it was very good because it was on the percentage 81%-100%.  In other words, the use of Al Arabia Baina Yadaik book was effective in increasing student Arabic speaking skills at the eighth grade of Islamic Junior High School of Darun Na’im Simpang Kubu, Kampar.